The Influence of Brand Trust on The Decision of Repurchasing Sari Roti Product (Case Study on Sari Roti Consumers) - Dania Rava Filda Zhia; Hawignyo Hawignyo (Primanomics : Jurnal Ekonomi & Bisnis, 2022)
Bakery companies in Indonesia are increasingly competitive, each company is required to develop skills and formulate appropriate and measurable marketing strategies to ensure business continuity and maintain brand trust . When customers have confidence in the brand, repeat buying behavior will be created. The purpose of this study was to determine the effect of Brand Trust on the Decision to Purchase Sari Roti Products. This study used descriptive and verification methods with a quantitative research approach. The sampling technique of this research is probability sampling with random sampling technique using the formula Isaac and Michael. The types of data used in this study are primary and secondary data. The data is processed using SPSS (Statistical Product and Service Solution) software . The results of this study prove that Brand Trust has a significant effect on Repurchase Decisions.